The Implication of Flipped Classroom Toward Students’ Reading Ability in English Class - Hakim, M. Arif Rahman; Rahayu, Septi; Rizal, Samsul; Bahari, Agustina Indah (Universitas Pancasakti Tegal, 2023)
The purpose of this study was to find out the Effect of Flipped Classroom toward Students’ Reading Ability in English Classroom. The sample of this study were the first grade students of Madrasah Aliyah or Islamic High School in Kaur Bengkulu, Indonesia. This study used a Quasi-Experimental design. The sample in this research was 52 students consisting of 26 students in the experimental class and 26 students in the control class taken by purposive sampling. The experimental class has given the treatment using the Flipped classroom strategy, while the control class used the conventional classroom strategy. Pre-test were given in two groups before giving the treatment. The results showed as follows: First, the average of pre-test score showed that the experimental class got 51.23 and the control class was 50,92. After being given treatment, a post-test is given. The post-test results show the average score of the experimental class was 71.85 and the control class was 62.85. The Second, the sample score of the independent T-test shows the significant value (2 tailed) is 0,000 <0.05. In other words, Ho was rejected and Ha was accepted. In short, it can be concluded that students who are taught using the Flipped Classroom strategy are better than not using it. So, it can be concluded that learning using flipped classroom has a positive effect on first grade students at Islamic High School in Kaur-Bengkulu Indonesia.